Pelatihan Penulisan Berita Berbahasa Inggris Berbasis Blog dan Genre Pedagogy untuk Meningkatkan Literasi Digital Santri Al-Mansyuriyah - Dwi Sloria Suharti; Gufron Gufron; Tatu Zakiyatun Nufus; Ade Mahmud; Hatami Hatami (Universitas Kristen Indonesia Toraja, 2026)
This community service program was conducted at Madrasah Aliyah/Pondok Pesantren Al-Mansyuriyah, Tangerang, to provide students with structured experience in English news writing and digital publication through blogs. The program responded to three main partner needs: limited experience in structured English news writing, limited use of blogs for publication, and the need to strengthen students’ digital literacy and writer identity. The activity was designed as a participatory and practice-based training program through three workshops: EFL News Writing, Blogging for EFL News Writing, and English Journal Writing. The evaluation used a pre-survey, a post-survey, observation, and documentation of student blog posts. The pre-survey involved 46 students; 31 students (67.4%) had written English news articles, but 42 students (91.3%) had never used blogs or written blog posts. The post-survey involved 45 students; all respondents (100%) reported that they understood ethical blog publication, and 42 students (93.3%) reported that they could use blogs, images, links, and videos to support their writing. The program produced six student blog posts on pesantren activities, National Santri Day, Teacher’s Day, new student admission, and literacy events. These findings indicate that blog-based genre pedagogy can provide an authentic medium for introducing EFL news writing, digital publication, ethical awareness, and students’ emerging writer identity. Further mentoring is needed to evaluate and improve the linguistic accuracy, news structure, and multimodal quality of students’ writing.